DNA Condensation Study of Fully Synthesized Lipopeptide-Based Transfection Agent for Gene Delivery Vehicle - Tarwadi Tarwadi; Heni Rachmawati; Rahmana E. Kartasasmita; Sabar Pambudi; Alfan Danny Arbianto; Dewi Esti Restiani; Sukmadjaja Asyarie (ANNALES BOGORIENSES, 2018)
The main requirement of transfection agent has to condense DNA in nanoparticle size, protect the DNA from nucleases and other degrading enzymes during its transport in cell cytoplasm and nucleus and should not toxic to target cells. In this research, lipopeptide composed of palmitoyl (C-16) and short peptide sequence have been designed fully synthesized and tested to DNA condensation capability and toxicity. The DNA condensation study was performed using EtBr exclusion assay and cytotoxicity determination was carried out by colorimetric MTT assay. It was revealed that lipopeptide-based transfection agent of Pal-CKKHH and Pal-CKKHH-YGRKKRRQRRR-PKKKRKV condensed DNA molecules efficiently. The lipopeptide was less toxic compared to Lipofectamine and Poly-L-Lysine, that shown by 90% of CHO-K1 cells remained viable when they were treated with 4.36 µM Pal-CKKHHYGRKKRRQRRR-PKKKRKV. Meanwhile, there were only ~75% and 80% of CHO-K1 viable cells when it was treated with PLL and Lipofectamine®2000, respectively. Moreover, cell viability of HepG2 was ~ 75% after treated with 2.18 µM of Pal-CKKHH-YGRKKRRQRRR-PKKKRKV and decreased to ~65% when the lipopeptide concentration increased to 8.72 M. In summary, the synthesized lipopeptide condenses DNA molecules efficiently, less toxic than Lipofectamine®2000 and PLL and has possibility to be explored as a non-viral gene delivery vehicle.